The Impact of Parental Violence on Adolescent Mental Health: An Identification Study on Beeng Island, Sangihe Islands Regency - Alfira Anastasia Dareho; Ishma Najya Zafira Purnama (Westscience Press, 2025)
Violence against children, especially that committed by parents, remains a serious issue in Indonesia and affects adolescents’ mental health, such as anxiety, stress, and low self-confidence. The rise in cases of verbal violence becomes an important reason to study the relationship between parental violent behavior and adolescents’ mental health. The study aims to identify the impact that young adults have on their mental health in Beng Island, Sangihe Islands County. Research uses a quantitative method with a Likert scale questionnaire. The population was 50 young people ages 12-21, sampled through a total sampling technique. Data are analysed descriptively and inferentially using SPSS. Studies show that parental violence has a significant impact on a teenager’s mental health, verified by tests t (sig. 0,000 0.05; T minus 5.390 > t minus Abel 1.677) and test f (sig. 0.00 < 0.05). These findings point out that the higher the rate of violence young people are exposed to, the worse their mental health. The study emphasized the importance of parents’ understanding of the effects of violence and the need for application of a positive upbringing to support the teen’s psychological well-being.